Sharia Fintech Service Adoption Among Cooperative and Non-Cooperative Users in Jakarta and West Java: An Empirical Tam Study - Siti Rabiah Magfiroh; Wiku Suryomurti (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study examines the factors influencing the adoption of Sharia FinTech among cooperative and non-cooperative users that can help them provide better and more efficient services. Moreover, this research uses the Technology Acceptance Model (TAM) method that has been modified using quantitative analysis by distributing online questionnaires with a total of 154 respondents in the DKI Jakarta and West Java provinces. Data processing and hypothesis testing were conducted using the Structural Equation Model (SEM) which showed that variables PU, PUE, TRU, BI, and PR have a significant impact on ATT. Meanwhile, BI, PR, and UI have been proven to influence TRU, PUE has been proven to influence PU, and ATT has been proven to influence INT. Additionally, GS and UI do not affect ATT, and PR does not affect TRU for users' adoption of Sharia FinTech services. This study contributes to the literature on Sharia FinTech service adoption by providing a more comprehensive view of user attitude determinants by combining trust in FinTech services with TAM.